Tumor-associated macrophages: A promising target for a cancer immunotherapeutic strategy. (November 2020) - Zhang, Si-Yu; Song, Xin-Yu; Li, Yang; Ye, Lin-Lin; Zhou, Qiong; Yang, Wei-Bing
Abstract: Macrophages, a type of myeloid immune cell, play essential roles in fighting against pathogenic invasion and activating T cell-mediated adaptive immune responses. As a major constituent of the tumor microenvironment (TME), macrophages play a complex role in tumorigenesis and tumor progression. They can inhibit tumor growth by releasing proinflammatory cytokines and exerting cytotoxic activities but principally contribute to tumor progression by promoting tumor proliferation, angiogenesis, and metastasis. The tumor-promoting hallmarks of macrophages have aroused widespread interest in targeting tumor-associated macrophages (TAMs) for cancer immunotherapy. Increasing preclinical and clinical studies suggest that TAMs are a promising target for cancer immunotherapy. To date, TAM-targeted therapeutic strategies have mainly been divided into two kinds: inhibiting pro-tumor TAMs and activating anti-tumor TAMs. We reviewed the heterogeneous and plastic characteristics of macrophages in the TME and the feasible strategies to target TAMs in cancer immunotherapy and summarized the complementary effect of TAM-targeted therapy with traditional treatments or other immunotherapies.